Volume 6B: Ocean Engineering 2020
DOI: 10.1115/omae2020-18214
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Non-Linear Boundary Conditions on the Wave Disturbance and Hydrodynamic Forces of Underwater Vehicles Travelling Near the Free-Surface

Abstract: This study compares the effect of non-linear free-surface boundary conditions for a high-order non-linear free-surface Rankine-source boundary element method on wave disturbance and hydrodynamic forces acting on an underwater vehicle travelling near a calm free-surface. In particular, simulations for a steady nonaxisymmetric prolate spheroid using different basis flows and linearization techniques were compared to an analytical method achieved by Chatjigeorgiou using a multipole expansion of Green’s functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Very few experimental results are available for reasonable comparison to the BEM, and another numerical solution is therefore explored. A short investigation showed that the nonlinear settings for the BEM used by Lambert and Brizzolara [14] are inconsistent with respect to depth; therefore, a Reynolds-Averaged Navier-Stokes Equations (RANSE) solver with the volume of fluid free-surface capturing is used. This simulation method is applied using an inviscid fluid so that conditions similar to potential flow can be achieved.…”
Section: Ranse Cfdmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few experimental results are available for reasonable comparison to the BEM, and another numerical solution is therefore explored. A short investigation showed that the nonlinear settings for the BEM used by Lambert and Brizzolara [14] are inconsistent with respect to depth; therefore, a Reynolds-Averaged Navier-Stokes Equations (RANSE) solver with the volume of fluid free-surface capturing is used. This simulation method is applied using an inviscid fluid so that conditions similar to potential flow can be achieved.…”
Section: Ranse Cfdmentioning
confidence: 99%
“…A transverse wave cut method [29] is applied to estimate the wave-making characteristics in each simulated case using the longitudinal wave slope along a perpendicular slice to the wave pattern located 0.6 body lengths (1.2 m) behind the stern. The transverse wave cut method has previously been used to identify nonlinearities in the wave patterns produced by the linear and nonlinear versions of the boundary element method used throughout this study [14]. This method has also been successfully applied to characterize the wave-making properties of high speed craft [30] and validated against other wave-cut methods [31].…”
Section: Wave Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Submarines frequently descend to periscope or snorkeling depths, for target exploration or ba ery recharging, wherein they encounter environmental loads, including waves, currents, resistance and suction forces [23,24]. Numerous studies have investigated the impact of the free water surface on underwater vehicles using both numerical and experimental methods [25][26][27][28][29][30][31][32][33][34][35]. Given the imposed forces experienced by submerged structures in different water depths, submarines must maintain specific navigational poses (depth, roll and trim angle), necessitating extensive research on depth control strategies.…”
Section: Introductionmentioning
confidence: 99%